2011
DOI: 10.1002/jbmr.528
|View full text |Cite
|
Sign up to set email alerts
|

A murine model of neurofibromatosis type 1 tibial pseudarthrosis featuring proliferative fibrous tissue and osteoclast-like cells

Abstract: Neurofibromatosis type 1 (NF1) is a common genetic condition caused by mutations in the NF1 gene. Patients often suffer from tissuespecific lesions associated with local double-inactivation of NF1. In this study, we generated a novel fracture model to investigate the mechanism underlying congenital pseudarthrosis of the tibia (CPT) associated with NF1. We used a Cre-expressing adenovirus (AdCre) to inactivate Nf1 in vitro in cultured osteoprogenitors and osteoblasts, and in vivo in the fracture callus of Nf1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 30 publications
(37 reference statements)
2
54
0
Order By: Relevance
“…Mice underwent a closed fracture (i.e., the periosteum remained intact) with injection of AdCre into the fracture site for transduction of local cells. As previously established 18 …”
Section: In Vivo Fluorescence Cell Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice underwent a closed fracture (i.e., the periosteum remained intact) with injection of AdCre into the fracture site for transduction of local cells. As previously established 18 …”
Section: In Vivo Fluorescence Cell Trackingmentioning
confidence: 99%
“…In 2012, we described a new surgical model of NF1 pseudarthrosis that features localized double inactivation of the Nf1 gene in a fracture 18 . In this model, Nf1 flox/flox mice are injected with a Cre-expressing adenovirus (AdCre) at the site of a tibial fracture, causing the local deletion of both Nf1 genes and resulting in a fibrous pseudarthrosis.…”
mentioning
confidence: 99%
“…We propose that the formation of periosteal hamartoma in congenital pseudarthrosis is due to abnormally high proliferation associated with poor differentiation capability of mesenchymal stem cells (El-Hoss et al, 2012) residing in the local periosteum due to non-functional negative regulation of Ras signalling pathway in neurofibromatosis (Abramowicz and Gos, 2013). Bisphosphonates should support the differentiation by regulating the Ras protein in BM MSCs (von Knoch et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology is unclear but there is a strong association between CPT and neurofibromatosis type I (NF-I). Histological examination has shown hyperplasia of fibroblasts within the periosteum [3][4][5] and a better understanding of the role of NF-1 has suggested that the defect results from failure of osteoblastic differentiation [6,7]. CPT is challenging to treat and, historically, amputation rates of up to 50 % have been reported [8,9].…”
Section: Introductionmentioning
confidence: 99%